2021
DOI: 10.3390/nano11040921
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Radiation Spectroscopy and Transmission Electron Microscopy Techniques to Evaluate TiO2 NPs Incorporation, Speciation, and Impact on Root Cells Ultrastructure of Pisum sativum L. Plants

Abstract: Biosolids (Bs) for use in agriculture are an important way for introducing and transferring TiO2 nanoparticles (NPs) to plants and food chain. Roots of Pisum sativum L. plants grown in Bs-amended soils spiked with TiO2 800 mg/kg as rutile NPs, anatase NPs, mixture of both NPs and submicron particles (SMPs) were investigated by Transmission Electron Microscopy (TEM), synchrotron radiation based micro X-ray Fluorescence and micro X-ray Absorption Near-Edge Structure (µXRF/µXANES) and Inductively Coupled Plasma O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…This could reflect the difficulty of these larger particles to enter the root and to move within the tissues. 56 Results were consistent with ATR-IR measurements confirmed that C. endivia seedlings absorbed more easily nPS.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This could reflect the difficulty of these larger particles to enter the root and to move within the tissues. 56 Results were consistent with ATR-IR measurements confirmed that C. endivia seedlings absorbed more easily nPS.…”
Section: Resultssupporting
confidence: 84%
“…This could reflect the difficulty of these larger particles to enter the root and to move within the tissues. 56 Results were consistent with ATR-IR measurements confirmed that C. endivia seedlings absorbed more easily nPS. Worthy of attention was the presence of plasmolysis in all tissues of all treated samples that could be related to a reduced water absorption.…”
Section: Transmission Electron Microscope (Tem) Observationssupporting
confidence: 84%
“…Also in this case, the treatments were able to alter the localization pattern of the probe, indicating the direct effects of the PSNPs on the integrity of the membranes, belonging to different tissues and organs. As demonstrated for metal nanoparticles (Muccifora et al, 2021) local production of ROS, would lead to the degradation of structures such as cell membrane and cell wall, allowing possible PSNPs entrance and movement. These data were supported by the observations at the TEM (Fig.…”
Section: Psnps Treatments Were Not Associated With Increase In Oxidat...mentioning
confidence: 99%
“…This suggests that treatment with nano-TiO 2 would induce root tissue damage by facilitating the entry and uptake of nano-PS into the plant body. In fact, in a previous work (Muccifora et al, 2021), it has been shown that anatases nano-TiO 2 are able to produce crossing ruptures of cell wall and plasmalemma of adjacent cell root, in this way enhancing nanoplastic uptake.…”
Section: Phenolsmentioning
confidence: 93%